Effects of Elemental Mercury Vapor Inhalation on Arterial Blood Gases, Lung Histology, and Interleukin-1 Expression in Pulmonary Tissues of Rats - Liqaa A. Raffee; Khaled Z. Alawneh; Ruba A. Alassaf; Abdallah Alzoubi; Musa A. Alshehabat; Nadeem Alabdallah; Abdel-Hameed Al-Mistarehi (The Scientific World Journal)
We investigated the effects of elemental mercury vapor inhalation on arterial blood gases (ABGs), lung histology, and interleukin-1 (IL-1) expression in pulmonary tissues in rats. A total of 42 Sprague Dawley rats were divided randomly into three groups. Rats in the first group were used as the control (CG). A short-term group (STG) and a long-term group (LTG) were exposed to 500 μg/m3 of mercury vapor 2 hrs/day for 21 days and 65 days, respectively. After exposure periods were completed, arterial blood samples were obtained, and ABGs were measured. Lung tissue sections were prepared for histology evaluation and immune-stained to detect IL-1 expression. There was a significant decrease in body weight in both STG (15%) and LTG (22%) compared with the CG. In the LTG, six out of 14 (43%) rats died, including two males and four females, while none of the rats in the STG died during the experiment. In both STG and LTG, a significant acid-base imbalance was characterized by a significant decrease in blood pH values and a significant increase in PCO2 values. Both PO2 and SpO2 blood values were significantly decreased in the STG and LTG, while no changes were observed in HCO3 values in all groups. Histological evaluation of lung tissues revealed severe lesions characterized by pulmonary emphysema and inflammatory cellular infiltrate. IL-1 expression in lung tissues was not significantly different between exposed rats and control subjects. These results indicate significant alterations in blood acid-base status characterized by severe respiratory acidosis with hypoxemia and no evidence of compensatory alkalosis in rats after exposure to short- and long-term elementary mercury vapor.